The Vocational High School Strategy in Increasing Partnerships with Business and Industry - Setiawan, Deny; Bafadal, Ibrahim; Supriyanto, Achmad; Hadi, Syamsul (Indonesian Research Journal in Education |IRJE|, 2024)
This research comprehensively examined vocational school management and strategies for improving partnerships with DUDI. This research used qualitative research and data collection techniques used observation, documents, and interviews. Data analysis on individual cases with condensation, data display, and conclusion drawing and verification used the N-Vivo tool. The research was at one vocational school in Blitar, Indonesia with informants from stakeholders at the school and industrial partners. The research site succeeded in establishing 14 partnerships recorded in the MoU, including joint activity programs, infrastructure utilization, program financing, and placement of graduates in the world of work. Partnership evaluation was carried out by monitoring the collaboration results, deliberation, adjustments to the MoU, consideration of student needs, and renewal to improve quality and collaboration.